2006
DOI: 10.1074/jbc.m604127200
|View full text |Cite
|
Sign up to set email alerts
|

PEGylation and Multimerization of the Anti-p185HER-2 Single Chain Fv Fragment 4D5

Abstract: A major goal in antibody design for cancer therapy is to tailor the pharmacokinetic properties of the molecule according to specific treatment requirements. Key parameters determining the pharmacokinetics of therapeutic antibodies are target specificity, affinity, stability, and size. Using the p185 HER-2 (HER-2)-specific scFv 4D5 as model system, we analyzed how changes in molecular weight and valency independently affect antigen binding and tumor localization. By employing multimerization and PEGylation, fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(96 citation statements)
references
References 67 publications
3
91
0
1
Order By: Relevance
“…We found that conjugation of a 40-kDa branched mPEG chain strongly increased the hydrodynamic radius of the protein from 2.7 to 7.9 nm as determined by SEC. Similar observations were made for other PEGylated recombinant antibodies (42). Thus, the increased circulation time is likely caused by a reduced renal clearance.…”
Section: Discussionsupporting
confidence: 68%
“…We found that conjugation of a 40-kDa branched mPEG chain strongly increased the hydrodynamic radius of the protein from 2.7 to 7.9 nm as determined by SEC. Similar observations were made for other PEGylated recombinant antibodies (42). Thus, the increased circulation time is likely caused by a reduced renal clearance.…”
Section: Discussionsupporting
confidence: 68%
“…S3-S4). The PEG20-containing proteins eluted at an apparent molecular weight of >300 kDa, consistent with the well-known effect of PEG20 of greatly increasing the hydrodynamic radius (26,28). PEGylation had previously been shown to have no effect on the off-rate and only a small effect on the on-rate (28).…”
Section: Resultsmentioning
confidence: 52%
“…For PEGylation of the DARPins, a cysteine was introduced at the penultimate position and the protein was allowed to react with maleimide-PEG of 20, 40, or 60 kDa. The scFv fragment 4D5 was expressed and purified in E. coli SB536 as previously described (26). HER2 (first 631 amino acids of the mature protein) was kindly provided by Dr. Tim Adams and coworkers (CSIRO, Melbourne, Australia).…”
Section: Methodsmentioning
confidence: 99%
“…Cependant, les nanobodies étant plus petits que la limite de filtration des glomérules rénaux, ils sont rapidement éliminés dans les urines. Pour éviter ce problème, une première approche consiste à coupler chimiquement une molécule de PEG (polyéthylène glycol) au dAb (PEGylation) [16]. Une solution bien plus élégante consiste à fusionner un dAb d'intérêt à un autre dAb affin pour l'albumine, protéine très abondante dans le sérum, conférant ainsi à la protéine de fusion un temps de demi-vie bien plus long, dépendant de l'affinité du dAb anti-albumine [17].…”
Section: Ingénierie Et Application Des Dabunclassified